Synaptic noise facilitates the emergence of self-organized criticality in the Caenorhabditis elegans neuronal network. (2nd October 2018) - Çiftçi, K.
ABSTRACT: Avalanches with power-law distributed size parameters have been observed in neuronal networks. This observation might be a manifestation of self-organized criticality (SOC). Yet, the physiological mechanisms of this behaviour are currently unknown. Describing synaptic noise as transmission failures mainly originating from the probabilistic nature of neurotransmitter release, this study investigates the potential of this noise as a mechanism for driving the functional architecture of the neuronal networks towards SOC. To this end, a simple finite state neuron model, with activity dependent and synapse specific failure probabilities, was built based on the known anatomical connectivity data of the nematode Ceanorhabditis elegans . Beginning from random values, it was observed that synaptic noise levels picked out a set of synapses and consequently an active subnetwork that generates power-law distributed neuronal avalanches. The findings of this study bring up the possibility that synaptic failures might be a component of physiological processes underlying SOC in neuronal networks.